Keberlanjutan UMKM olahan hasil laut di Pesisir Bulak Surabaya guna meningkatkan daya saing di era new normal (Sustainability of MSMEs processed marine products in Bulak Coastal Surabaya to increase competitiveness in the new normal era) - Wurlina, W; Racmawati, Kadek; Utama, Suzanita; Mahasri, Gunanti; Mulyati, Sri; Suwasanti, Niluh (Universitas Syiah Kuala, 2022)
The Regional Leading Product Development Program (RLPDP) activities are carried out to sustain the existence of Micro, Small, and Medium Enterprises (MSMEs) processed marine products in increasing marketing in the new normal of the Covid-19 Pandemic period. This makes the implementation team assist the strategies used by MSMEs and the effectiveness of these strategies. In this activity, the factors influencing MSMEs sustainability were product innovation, packaging, and marketing. The method used was education, training, and mentoring for the innovation of processed seafood using packaging according to its function and marketing. The result of RLPDP was MSMEs have implemented innovations in processed marine products with packaging accompanied by the length of use, labeling, business permits, and halal accompanied by slogans. Marketing of seafood products processing was carried out through the Surabaya UKM center, namely the Siola MSMEs Center, the SIB (Bulak Fish Center) MSMEs, Merr MSMEs, hotels, and participation in exhibition activities organized by the Surabaya City Government and East Java Province. Furthermore, to expand marketing reach, socialization has been carried out through social media such as WhatsApp, Facebook, Instagram, and e-mail, as well as the marketplaces such as Tokopedia, Bukalapak, and Blibli.